CARMAL Is a Long Non-coding RNA Locus That Regulates MFGE8 Expression - Soubeyrand, Sébastien; Nikpay, Majid; Lau, Paulina; Turner, Adam; Hoang, Huy-Dung; Alain, Tommy; McPherson, Ruth (Frontiers in Genetics, 2020)
Genome-wide association studies have identified several genetic loci linked to cardiovascular disease (CAD) most of them located in non-protein coding regions of the genome. One such locus is the CAD Associated Region between MFGE8 and ABHD2 (CARMA), a ~ 18 kb haplotype that was recently shown to regulate vicinal protein coding genes. Here, we further investigate the region by examining a long non-coding RNA gene locus (CARMAL/ RP11-326A19.4/AC013565) abutting the CARMA region. Expression-genotype correlation analyses of public databases indicate that CARMAL levels are influenced by CAD associated variants suggesting that it might have cardioprotective functions. We found CARMAL to be stably expressed at relatively low levels and enriched in the cytosol. CARMAL function was investigated by several gene targeting approaches in HEK293T: inactive CRISPR fusion proteins, antisense, overexpression and inactivation by CRISPR-mediated knock-out. Modest increases in CARMAL (3-4x) obtained via CRISPRa using 3 distinct single-guided RNAs did not result in consistent transcriptome effects. By contrast, CARMAL deletion or reduced CARMAL expression via CRISPRi increased MFGE8 levels, suggesting that CARMAL is contributing to reduce MFGE8 expression under basal conditions. While future investigations are required to clarify the mechanism(s) by which CARMAL acts on MFGE8, integrative bioinformatic analyses of the transcriptome of CARMAL deleted cells suggest that this locus may also be involved in leucine metabolism, splicing, transcriptional regulation and Shwachman-Bodian-Diamond syndrome protein function.